Green finance in Pakistan: Barriers and solutions - Sadia Malik; Maha Qasim; Hasan Saeed (Asian Development Bank Institute (ADBI), 2018)
Pakistan had been mired in a crippling energy crisis for several years but is experiencing a rapid turnaround in the energy sector with several new projects coming online. However, the interventions undertaken by the government rely heavily on imported fuel such as oil, coal, and LNG. An import-driven energy policy is not sustainable for Pakistan. Besides being a drain on its foreign exchange reserves, it exposes the economy to international energy price shocks, putting the entire economy at risk. A green energy-based energy policy can help Pakistan meet its energy requirements while reducing its dependence on imports and hence reduce the cost of energy to the country. This paper describes how the regulations and the structure of the power market support the financial viability of renewable energy in Pakistan and enable easy access to financing. The one-buyer, take-or-pay model of power purchase ensures that any new power project that may produce expensive power but provides other benefits like clean energy or an improvement in the balance of payments (use of local fuel instead of imported fuel) can be financially viable provided the government of Pakistan approves the project. However, the increased financial viability and bankability comes at the cost of higher energy prices to consumers due to low operational efficiencies and a higher subsidy burden on the government. The paper also discusses the challenges faced by distributed renewable energy projects (like home rooftop solar energy solutions) since they do not benefit from the same one-buyer, take-or-pay support. However, alternative schemes like subsidized financing can help in increasing the penetration of this source of energy.
Keywords: Q42; Q48; 330; Pakistan energy sector; green finance; energy policy